2021
DOI: 10.1007/s00441-021-03539-z
|View full text |Cite
|
Sign up to set email alerts
|

P75 neurotrophin receptor controls subventricular zone neural stem cell migration after stroke

Abstract: Stroke is the leading cause of adult disability. Endogenous neural stem/progenitor cells (NSPCs) originating from the subventricular zone (SVZ) contribute to the brain repair process. However, molecular mechanisms underlying CNS disease-induced SVZ NSPC-redirected migration to the lesion area are poorly understood. Here, we show that genetic depletion of the p75 neurotrophin receptor (p75NTR−/−) in mice reduced SVZ NSPC migration towards the lesion area after cortical injury and that p75NTR−/− NSPCs failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In the brain, new neurons are produced in the SVZ around the ventricle and the SGZ in the hippocampus, where neurogenesis occurs most actively and continuously [ 25 , 26 ]. Many studies have shown that when the brain is abnormal, the dividing neuroblasts move to the lesion location, and the migrated cells surround the lesion and slow its progression [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, new neurons are produced in the SVZ around the ventricle and the SGZ in the hippocampus, where neurogenesis occurs most actively and continuously [ 25 , 26 ]. Many studies have shown that when the brain is abnormal, the dividing neuroblasts move to the lesion location, and the migrated cells surround the lesion and slow its progression [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This reparative mechanism involves restoring damaged tissue and containing future expansion of the lesion. 51 Nevertheless, the quantity of activated endogenous NSCs within the organism is constrained. Furthermore, many of these endogenous NSCs tend to develop into glial cells due to adverse microenvironmental conditions.…”
Section: How Effective Is Neural Stem Cell Therapy For Ischemic Strokementioning
confidence: 99%
“…Neurogenesis has a pivotal role in the recovery process of the brain after stroke. Recently, Deshpande et al (2022) demonstrated the critical contribution of p75NTR to the migration of neural stem cells, which were produced in the SVZ after stroke [ 51 ]. It was revealed that p75NTR KO mice exhibited reduced SVZ neural stem cell migration towards the lesion area after cortical brain injury [ 51 ].…”
Section: Roles Of Bdnf/trkb System In Cns Neuronsmentioning
confidence: 99%